1989
DOI: 10.1021/bi00445a054
|View full text |Cite
|
Sign up to set email alerts
|

Role of histidine 64 in the catalytic mechanism of human carbonic anhydrase II studied with a site-specific mutant

Abstract: To test the hypothesis that histidine 64 in the active site of human carbonic anhydrase II functions as a proton-transfer group in the catalysis of CO2 hydration, we have studied a site-specific mutant having histidine 64 replaced by alanine, which cannot transfer protons. The steady-state kinetics of CO2 hydration has been measured as well as the exchange of 18O between CO2 and water at chemical equilibrium. The results show that the rate of exchange between CO2 and HCO3- at chemical equilibrium is essentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
423
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 402 publications
(442 citation statements)
references
References 23 publications
19
423
0
Order By: Relevance
“…A conformational change is observed for His-64, the catalytic proton shuttle (Steiner et al, 1975;Tu et al, 1989); the imidazole side chain undergoes a rotation of 58°a bout side chain torsion angle 1 to the "out" conformation (data not shown), as observed in certain CAII structures (e.g. see Nair and Christianson (1991)).…”
Section: Resultsmentioning
confidence: 92%
“…A conformational change is observed for His-64, the catalytic proton shuttle (Steiner et al, 1975;Tu et al, 1989); the imidazole side chain undergoes a rotation of 58°a bout side chain torsion angle 1 to the "out" conformation (data not shown), as observed in certain CAII structures (e.g. see Nair and Christianson (1991)).…”
Section: Resultsmentioning
confidence: 92%
“…The intramolecular proton transport occurs between the Zn-bound solvent and the side chain of His64, which is located on the edge of the active site, where the proton is further transferred out to the bulk solvent (eq 2). The mutation of His64 to an alanine (H64A HCA II) reduces the proton transfer activity 10-to 50-fold (7). Various crystal structures, determined at different pH values, have revealed that His64 occupies dual conformations, the socalled "in", pointing inward toward the active site, and "out", pointing outward away from the active site, and it is thought that the apparent flexibility of His64 is essential to its function as an efficient proton shuttle ( Figure 1) (8,9).…”
mentioning
confidence: 99%
“…experiments). Movement of the side chain of His-64 has also been implicated in the enzyme mechanism (Tu et al, 1989;Krebs et al, 1991;Nair & Christianson, 1991). Therefore, the observation of a change in the position of the side chain of His-64 between the native enzyme (Eriksson et al, 1988) and that inhibited by I C (Baldwin et al, 1992) (Fig.…”
mentioning
confidence: 99%